On the Occurrence of Cheirotonus gestroi (Scarabaeidae: Coleoptera) in Mizoram, Northeastern India: Molecular and Morphological Characterization - Zothansanga, Chawngthu; Malsawmdawngzuali, Tara; Zodinpuii, Betsy; L, Lalramliana (Asian Journal of Biological and Life Sciences, 2025)
Aim: This study aimed to validate the presence of Cheirotonus gestroi in Mizoram, North-eastern India, expanding its geographical distribution, and providing detailed morphological descriptions, particularly focusing on sexual dimorphism, for future identification. Materials and Methods: Specimens were collected from Murlen National Park (23.645ºN 93.29222ºE), Champhai district of Mizoram using light traps. After collection, the specimens were preserved in 70% alcohol for further analysis. The specimens were identified based on distinguishing morphological features and confirmed through molecular analysis by sequencing a partial segment of the mitochondrial 16S rRNA gene. Results: The results confirmed the presence of Cheirotonus gestroi in Mizoram, North-eastern India. This marks the first recorded instance of the species in Mizoram. Morphologically, C. gestroi was distinguished from other Cheirotonus species by having orange-spotted elytra, the male apical protibial spine longer than the median spine, and medially toothed, a feature that sets it apart from similar species in the region. Analysis of the 16S rRNA gene confirmed the identity of the species. Conclusion: This study confirms the presence of Cheirotonus gestroi in Mizoram, broadening its known distribution. The findings provide important morphological descriptions and sexual dimorphism in particular and further contribute to the understanding of the species' ecological significance. The molecular confirmation through 16S rRNA gene sequencing further enhances the accuracy of the species identification. The study also underscores the need for biodiversity surveys and highlights the importance of conservation efforts in protecting such species.
Keywords: Biodiversity hotspot; Genitalia; Occurrence; Sexual Dimorphism